2011
DOI: 10.1080/14780880903061812
|View full text |Cite
|
Sign up to set email alerts
|

Felt Stigma in Injection Drug Users and Sex Workers: Focus Group Research with HIV-Risk Populations in Puerto Rico

Abstract: Though many studies have conclusively linked felt stigma and HIV, few have focused on the experiences of rejection felt by members of such socially marginalized groups as intravenous drug users (IDU) and sex workers (SW). Using focus groups, our study explored these experiences in 34 individuals (17 male UDUs and 17 female SWs) at risk of becoming infected with HIV, the objective being to discover why they engaged in maladaptive behaviors as a way of coping with felt stigma. We used deductive and inductive ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…The rate of social stigma in unsafe sexual behavior was higher than other ways of transmission. Previous findings were consistent with the results of our study [26][27][28], and others had conflicting results [20]. Herrick et al reported that high-risk behaviors, especially sexual relationships, bear the brunt of social stigma in society [29].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The rate of social stigma in unsafe sexual behavior was higher than other ways of transmission. Previous findings were consistent with the results of our study [26][27][28], and others had conflicting results [20]. Herrick et al reported that high-risk behaviors, especially sexual relationships, bear the brunt of social stigma in society [29].…”
Section: Discussionsupporting
confidence: 91%
“…The number of sample was determined using following formula: α (two-tailed) = 0.05 β = 0.20 r = 0.34 (expected correlation coefficient between emotional social support and HIV patient) [16] Sample size = N = [(Z α + Z β )/C] 2 + 3 = 102, where standard normal deviate for α = Z α = 1.96, standard normal deviate for β = Z β =1. 28, and C = 0.5 × ln [(1 + 0.34)/ (1 -0.34)] = 0.354. Total samples were selected by simple random sampling.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, those with negative attitudes towards injection drug users held more stigmatizing AIDS attitudes (26, 28). Further, drug injection users affected by HIV cite the stigma of drug injection use as a major reason for delaying medical care (58, 59). …”
Section: Discussionmentioning
confidence: 99%
“…A high proportion of people who use injection drugs live also with HIV [1,2,13], hepatitis C [13][14][15][16][17][18][19], and hepatitis B [13,18,20]. People who inject drug are often marginalized and are socially stigmatized and discriminated within health and social care settings [21][22][23]. People who inject drugs are prone to problems difficult to accept in a legal environment.…”
Section: Introductionmentioning
confidence: 99%